2013
DOI: 10.3126/on.v11i1.8238
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Studies of Chromium by Using Low Cost Adsorbents

Abstract: The presence of toxic heavy metals such as chromium (VI) contaminants in aqueous streams, arising from the discharge of untreated metal containing effluents into water bodies, is one of the most important environmental problems. Adsorption is one of the effective techniques for chromium (VI) removal from wastewater. In the present study, adsorbent was prepared from low cost adsorbents and studies were carried out for chromium (VI) removal. Batch adsorption studies demonstrated that the adsorbents had significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
4
0
1
Order By: Relevance
“…The highest chromium removal percentage (99.75%) by dry alga, Chlorella vulgaris, was obtained using 60 mg/50 mL solutions (1.2 g/L) 70 . Gandhi et al 72 demonstrated that the highest percentage uptake of chromium was obtained with 8.0 g algae as biosorbent. The highest chromium removal (83.55%) was obtained with 0.6 g/L Sargassum sp.…”
Section: Effect Of Malachite Green Concentrations the Percentage Of mentioning
confidence: 99%
“…The highest chromium removal percentage (99.75%) by dry alga, Chlorella vulgaris, was obtained using 60 mg/50 mL solutions (1.2 g/L) 70 . Gandhi et al 72 demonstrated that the highest percentage uptake of chromium was obtained with 8.0 g algae as biosorbent. The highest chromium removal (83.55%) was obtained with 0.6 g/L Sargassum sp.…”
Section: Effect Of Malachite Green Concentrations the Percentage Of mentioning
confidence: 99%
“…Penyerapan ion Cr(VI) oleh adsorben dari rumput laut (Fucus vesiculosus) dibuktikan dengan analisis FT-IR terdapat gugus hidroksil (-OH) dan gugus amino yang berkurang setelah adsorbsi yang menyebabkan ion Cr(VI) terikat pada permukaan adsorben (Cobas, Saronman, & Pazos, 2014). Salah satu pemanfaatan limbah biomassa dijadikan sebagai adsorben adalah adsorben dari cangkang Arenga pinnata merr untuk logam Cr(III) dan Cr(VI) (Zein, Arrisujaya, Hidayat, Elfia, Nazarudin, & Munaf., 2014), Adsorben dari limbah sekam dan jerami padi Singha, Naiya, Bhattacharya, & Das, 2011;Kumar, Arya, Singh, & Vats, 2017), akar eceng gondok (Singha et al, 2011); tempurung kelapa (Singha et al, 2011), kulit kayu pohon mangga, batu bata, batu kapur, bubuk biji pepaya dan Alga (Gandhi, Sirisha, & Sekhar, 2013) dapat dimanfaatkan untuk mengurangi cemaran ion logam Cr(VI), adsorben dari biji alpukat untuk logam Cu(II), Pb(II) dan Cd(II) (Wanja, Murungi, Wanjau & Hassanali, 2015).…”
Section: Pendahuluanunclassified
“…Rapid population growth and agricultural development resulting from industrial activities release numerous organic and inorganic pollutants into nature. [1][2][3] These pollutants can be discharged into both aquatic and terrestrial environments. Discharging wastewater into water bodies adversely affects water quality, the environment, and public health.…”
Section: Introductionmentioning
confidence: 99%